Elements of Emotional Intelligence in Bhagwad Geeta - Naveen Kumar, Kuldeep Singh (International Journal of Advanced Science and Technology, 2019)
Every living things has their own emotions by which they introduce themselves, even plants has also their emotions with different situations shows their feelings i.e. Mimosa pudica it’s a plant which when touched, contracts its leaves. It’s called Mimosa pudica in scientific language, Touch-Me-Not Plant as a common name and "Chui Mui" in Hindi Language. There are different kinds of emotions in humans like crying, happiness, sadness, sorrow etc. are emotion by them human shows their feelings without speaking. Emotionally independency is requiring living happily, Present world is fully dependent on each other’s to live or behave. In India, ancient texts like BhagwadGeeta use to describe Emotional intelligence. They describe how emotions are directly connected with our desires; ancient yogic texts are totally based on science which modern science can’t explain. In this study we are trying to explain how emotional intelligence is descried in Bhagwadgeeta& other texts